Effect of cooling and freezing on the kinematic parameters of ram spermatozoa sexed by modified protocol with TLR7/8 ligand R848 - Yotov Stanimir; Kistanova Elena; Atanasov Anatoli; Ivanova Boyana; Zaimova Darina (Biotechnology in Animal Husbandry)
The present study investigated the effect of sex-sorting by TLR7/8 ligand R848, cooling and cryopreservation on the motility and kinematic characteristics of ram spermatozoa for the first time. Four ejaculates per ram (n=2) were collected, pooled and after that were split to 8 equal parts. Four parts were used for sexing and four parts were analyzed as unsexed semen. The sperm sexing was done by application of the TLR7/8 ligand R848 (resiquimod). Diluted with freezing extender unsexed and sex-sorted semen were cooled in a refrigerator at temperature 5°C for 5 hours and after that freeze/thawed. Each part of semen at each step of the experiment was subjected to computer assisted semen analysis for evaluation of motility and speed parameters of spermatozoa. After sexing the significant reducing of kinematic parameters in both fractions were observed. The dilution of sexed spermatozoa with freezing extender before cooling reliably increased the progressive motility and speed parameters as VCL, VAP, and VSL in Xand Y-fractions and kept them during the cooling at relatively high level. Freezing adversely impaired the motility of sexed spermatozoa. The values of speed parameters of unsexed spermatozoa after thawing were significantly higher than those of X and Y spermatozoa. Dilution with an appropriate freezing extender and cooling are most suitable approaches for storing of sexed ram spermatozoa.